Noisy Label Calibration for Multi-View Classification - Xu, Shilin; Sun, Yuan; Li, Xingfeng; Duan, Siyuan; Ren, Zhenwen; Liu, Zheng; Peng, Dezhong (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
In recent years, multi-view learning has aroused extensive research passion. Most existing multi-view learning methods often rely on well-annotations to improve decision accuracy. However, noise labels are ubiquitous in multi-view data due to imperfect annotations. To deal with this problem, we propose a novel noisy label calibration method (NLC) for multi-view classification to resist the negative impact of noisy labels. Specifically, to capture consensus information from multiple views, we employ max-margin rank loss to reduce the heterogeneous gap. Subsequently, we evaluate the confidence scores to enrich predictions associated with noise instances according to all reliable neighbors. Further, we propose Label Noise Detection (LND) to separate multi-view data into a clean or noisy subset, and propose Label Calibration Learning (LCL) to correct noisy instances. Finally, we adopt the cross-entropy loss to achieve multi-view classification. Extensive experiments on six datasets validate that our method outperforms eight state-of-the-art methods.